Portable System for Rapid Field Test of CEA in Human Serum Based on Chemiluminescence Enzyme Immunoassay. Issue 1 (1st January 2017) - Liu, Juntao; Qu, Shuxue; Luo, Jinping; Wang, Bin; Cai, Xinxia
Abstract : Carcinoembryonic antigen (CEA) is one of the most widely used tumor markers worldwide. A portable system was designed for rapid field specific test of CEA based on immunomagnetic separation and chemiluminescence immunoassay, which consisted of chemiluminescent immunosensor and optical test instrument. The chemiluminescent immunosensor was based on immunomagnetic separation and chemiluminescence immunoassay, which utilized a immuno‐sandwich scheme as‐say with Horseradish peroxidase (HRP) labeled anti‐CEA antibody and Immunomagnetic beads (IMBs). And the test instrument consisted of optical detection module and central processing and control system. The optical noise of this instrument was below 40 photons/s. The system could achieve a sample test in 30 minutes, and the detecting result showed a good liner relationship between the intensity of luminescence and concentration of CEA in the range from 1 to 1000ng/mL, with a correlation coefficient of 0.9858. Real human samples were also detected with this system in comparison with clinical results and a correlation coefficient of 0.9934 was obtained. The instrument is portable and easy to operate, which will provide potential application in cancer clinical test.